A Critical Analysis on the Impact of IT to the Overall Performance of Executive Secretaries in the Public Sector of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Information technology provides effectiveness of functioning and better productivity in the operations of an organization and public sector is not an exception. In the public sector of Oman, the use of information technology has made a specific role that has added to the quality and quantity of performance that has enriched the productivity of the public sector of Oman. The study here evaluates the impact of IT to the overall performance of executive secretaries in the public sector of Oman. There are different stages that are adopted by the researcher in order to attain the objectives. The study adopts data collection from 100 executive secretaries that are chosen from five of the public sectors to provide opinion regarding the topic of study. The research has presented a detailed literature review of the topic that clarifies the subject on which the topic is based and a critical evaluation of the gathered literature is also provided through the study. The study here adopts a descriptive research that is conducted through survey which is done through the prepared questionnaire distributed to the selected respondents. The opinion is presented through data analysis and the results are presented through the structure of chart and tables for easy identification of the opinion, views and suggestions from the participants that have added to the attainment of the objective. The main findings of this study suggest that the executive secretaries ought to be trained in IT skills and motivated to improve their innovation and their work performance. Besides the online IT training, this study recommended the improvement of the automation in the daily tasks of the executive secretaries in Oman.